Analysis of the Influence of Hybrid and Remote Work Systems on Employee Performance and Productivity in Start-Ups: Work-Life Balance as a Mediating Variable - Chelsea Vanessa; Liestyaningrum Rahmadhani Wisnu Putri (Amkop Management Accounting Review (AMAR), 2026)
The post-pandemic paradigm shift in work arrangements has driven the massive adoption of hybrid and remote work systems in start-up companies; however, their impact on employee performance and productivity has not been comprehensively examined considering the mediating role of work-life balance. This study aims to analyze the influence of hybrid and remote work systems on work-life balance, performance, and productivity of start-up employees, as well as to examine the role of work-life balance as a mediating variable. A quantitative survey method was employed with 300 start-up employee respondents in Indonesia, analyzed using multiple linear regression and the Sobel Test. The results indicate that both hybrid and remote work systems have a significant positive effect on work-life balance, employee performance, and productivity. The hybrid system demonstrates a more dominant influence on work-life balance and productivity, while the remote system is more prominent in affecting individual performance. Work-life balance is proven to significantly mediate all relational pathways, with the strongest mediation effect found on the hybrid system's pathway to productivity (T = 4.308; p = 0.000). These findings imply that optimizing work-life balance is a key strategy in maximizing the impact of flexible work systems on start-up employee performance.